Reflecting on the Essence of our Problem-Based Learning Discussions: The Importance of Faculty Development and our Continuous Quest for Applications of Problem-Based Learning - Engle Angela Chan (Kaohsiung Journal of Medical Sciences, 2009)
While problem-based learning (PBL) is a teaching strategy to promote critical thinking, creativity and self-directedness in learning is very important. It is the meaning of the learning, with a contextual understanding, that marks the significance of this approach in our healthcare education. At the 2008 Kaohsiung Medical University International Conference and Workshop on PBL, the scholarly discourse on sharing empirical findings and practical experience with various aspects of PBL brought forth the importance of the teachers' continued learning about the meaning, the dynamics of the process, and the pragmatic details of PBL. This quest for a continuous learning and understanding about PBL parallels our search to extend the classroom PBL into students' clinical experience. The development of clinical teachers in the understanding of PBL was explored as part of their experiential learning in clinical teaching after their PBL workshops. While the clinical teachers who participated in the project appreciated the merits of clinical PBL, the complex balance between patient service and student teaching—in an unpredictable clinical setting—has led to the use of a simulated clinical environment with simulated patients. We also piloted PBL for interprofessional education of undergraduate students of nursing and social work. The ways we can adopt PBL in various settings with different intents will help prepare our healthcare graduates in meeting the challenges of our ever more complex healthcare systems, and the demands of holistic patient care.